An Error Analysis of Students’ Recount Text Writing at SMA Negeri 2 Kefamenanu - Yanuarius Seran; Mikhael Misa; Nurul Fikriyah Isu; Eugelin Sulaiman; Maria Wihelmina Wisrance; Maria Fridolin Naben (Smart Edu Center, 2026)
This research aimed to find out the types of errors made by the tenth-grade students in writing recount text and to explore the problems they encountered during the writing process. This research used a mixed-method design (quantitative and qualitative) and involved 20 students of the tenth grade of SMAN 2 Kefamenanu in the 2024/2025 academic year. The data were collected through a writing test and semi-structured interview. Students’ writing errors were catogorised using surface strategy taxonomy comprising omission, addition, misformation, and misordering. The result revealed that students produced 318 errors. Misformation was the most the most frequent error, with 132 errors or 41.50%, followed by misordering with 70 errors or 22.01%, omission with 62 errors or 19.49%, and addition with 54 errors or 16.98%. The interview results revelaed that problems students encountered were (1) limited vocabulary, (2) sentence construction (3) paragraph organisation comprehension, (4) grammar rules mastery, (5) inadequate writing practice time. It is advised that teachers are supposed to provide more guided writing practice with adequate time, vocabulary enrichment, and grammar enrichment to facilitate students’ writing skill.